Hubungan Pendidikan, Pengetahuan dan Asupan Energi dengan Kejadian Underweight pada Balita di Desa Denai Sarang Burung - Suraya, Rani; Arika, Romiza; Khairunisa, Jeny (Media Gizi Ilmiah Indonesia, 2024)
Nutrition is an important part of supporting the growth and development of children under five. Children under five who have good nutritional status are a nutritional investment to support improving the quality of human resources in the future. This study aims to determine the relationship between maternal education and knowledge and toddler food intake with the incidence of underweight in Denai Sarang Burung Village, Pantai Labu District, Deli Serdang Regency. This type of quantitative research with a cross sectional design was conducted on 40 mothers of children under five. The sample was determined by pursive sampling. Data was collected by conducting interviews and observations guided by questionnaires related to education and knowledge, while data on toddlers' food intake was obtained using 2x24 hour food recall. Data analysis was carried out univariately to describe the picture of each variable studied. Bivariate analysis used the chi-square test to determine whether there was a relationship between education, knowledge and energy intake and the incidence of underweight. Based on the research results, the probability values ​​for the education, knowledge and energy intake variables were 0.049, 0.002 and 0.000 respectively. The research conclusion shows that there is a relationship between maternal education, maternal knowledge and energy intake with the incidence of underweight. A knowledge improvement program is needed to reduce the problem of underweight among toddlers so that the quality of human resources can be better.